Monophosphoryl lipid A alleviated radiation‐induced testicular injury through TLR4‐dependent exosomes. Issue 7 (5th March 2020) - Liu, Zhe; Cao, Kun; Liao, Zebin; Chen, Yuanyuan; Lei, Xiao; Wei, Qun; Liu, Cong; Sun, Xuejun; Yang, Yanyong; Cai, Jianming; Gao, Fu
Abstract: Radiation protection on male testis is an important task for ionizing radiation‐related workers or people who receive radiotherapy for tumours near the testicle. In recent years, Toll‐like receptors (TLRs), especially TLR4, have been widely studied as a radiation protection target. In this study, we detected that a low‐toxicity TLR4 agonist monophosphoryl lipid A (MPLA) produced obvious radiation protection effects on mice testis. We found that MPLA effectively alleviated testis structure damage and cell apoptosis induced by ionizing radiation (IR). However, as the expression abundance differs a lot in distinct cells and tissues, MPLA seemed not to directly activate TLR4 singling pathway in mice testis. Here, we demonstrated a brand new mechanism for MPLA producing radiation protection effects on testis. We observed a significant activation of TLR4 pathway in macrophages after MPLA stimulation and identified significant changes in macrophage‐derived exosomes protein expression. We proved that after MPLA treatment, macrophage‐derived exosomes played an important role in testis radiation protection, and specially, G‐CSF and MIP‐2 in exosomes are the core molecules in this protection effect.